PERANAN ORANG TUA DALAM MENCEGAH TAWURAN ANTAR PELAJAR - Ingtyas, Fatma Tresno (Universitas Negeri Medan, 2017)
Brawl is a negative interaction and has fatal consequences. Brawl between students nowadays is a very annoying problem of order and security in the surrounding environment. Interschool student brawls seem to have become a black spot in the world of education in Indonesia. According to the records of the National Commission for Child Protection (Komnas PA), the incidence of fights during the year 2011 has claimed 82 lives, not including the wounded. Each year the fight was not the case on the wane, but it is growing. Brawl between students arise as a result of excessive solidarity , as a result of mental thuggery, internal factors ( lack of religious upbringing, the influence of friends), and external factors (lack of parental and economic factors), are all factors brawl between students. Education in the family (parents) are very important as a basic foundation that forms the character of the child from the beginning. The role of parents is not only limited to instill norms of early life. They should continue to play an active role, especially when the children hit their teens, where these kids started looking for identity. 1) Building the Moral Development of the Child, 2) Parents follow the development of children's moral behavior, 3) Establish good communication with children, 4) Keeping family harmony, 5) Giving the correct approach to religion, and 6) As a true Mediator.